Edward Schillebeeckx’ theologie van de religies - Wiele, Jan van (Tijdschrift voor theologie, 2010)
Like many other theologians of the twentieth century, Edward Schillebeeckx has tackled the still very actual and urgent problem of the relationship between universality and particularity of Christianity vis-à-vis the other religions. He elaborated this especially in his solid article ‘Identiteit, eigenheid en universaliteit van Gods heil in Jezus’, in Tijdschrift voor Theologie (1990). In good scholastic tradition, he summarises the crucial aspects of this problem in the form of eight theses. In an overview, the principles of Schillebeeckx’s theology of religions will here be extracted from these theses. Because of the restricted frame of the essay and the complexity of the topic, his eight theses are somewhat rearranged on the basis of the dominant topics in the discussion: a plurality of religions, the singularity and universality of Christianity, the mystical character of Christianity and mission as dialogue. The thesis of this article is that Schillebeeckx has searched for a ‘via media’ between the classical insights of Thomistic theology, with which he was raised as a Dominican and as a theologian of the twentieth century, and the legitimate demand for a most ample recognition of truth and salvation that are also present in other religions. But Schillebeeckx’s answer, although very dialogical, carries the discussion a bit further than classical Thomistic theology, which raises a few questions that can only be touched on.